Nanoformulation Shows Cytotoxicity against Glioblastoma Cell Lines and Antiangiogenic Activity in Chicken Chorioallantoic Membrane - Danieli Rosane Dallemole; Thatiana Terroso; Aline de Cristo Soares Alves; Juliete Nathali Scholl; Giovana Ravizzoni Onzi; Rodrigo Cé; Karina Paese; Ana Maria Oliveira Battastini; Silvia Stanisçuaski Guterres; Fabrício Figueiró; Adriana Raffin Pohlmann (MDPI AG, 2021)
Glioblastoma (GB) is a histological and genetically heterogeneous brain tumor that is highly proliferative and vascularized. The prognosis is poor with currently available treatment. In this study, we evaluated the cytotoxicity and antiangiogenic activity of doxorubicin-loaded-chitosan-coated-arginylglycylaspartic acid-functionalized-poly(ε-caprolactone)-alpha bisabolol-LNC (AB-DOX-LNC-L-C-RGD). The nanoformulation was prepared by self-assembling followed by interfacial reactions, physicochemically characterized and evaluated in vitro against GB cell lines (U87MG and U138MG) and in vivo using the chicken chorioallantoic membrane assay (CAM). Spherical shape nanocapsules had a hydrodynamic mean diameter of 138 nm, zeta potential of +13.4 mV, doxorubicin encapsulation of 65%, and RGD conjugation of 92%. After 24 h of treatment (U87MG and U138MG), the median inhibition concentrations (IC50) were 520 and 490 nmol L−1 doxorubicin-equivalent concentrations, respectively. The treatment induced antiproliferative activity with S-phase cell-cycle arrest and apoptosis in the GB cells. Furthermore, after 48 h of exposure, evaluation of antiangiogenic activity (CAM) showed that the relative vessel growth following treatment with the nanocapsules was 5.4 times lower than that with the control treatment. The results support the therapeutic potential of the nanoformulation against GB and, thereby, pave the way for future preclinical studies.